Graphene oxide decorated with Ag and CeO2 nanoparticles as a catalyst for room-temperature 4-nitrophenol reduction - Taratayko, Aleksey V. (Catalysts)
Catalytic reduction of nitroaromatic compounds (NCs) into corresponding aminoaromatic compounds (ACs) addresses two challenges: enhancing of the manufacture scale of ACs as valuable chemical intermediates and removal of NCs as widespread wastewater pollutants. Among the noble metal catalysts that feature low-temperature activity, chemical stability, and nontoxicity, silver-containing catalysts are attractive as cost-efficient and easily prepared compositions. This paper is devoted to the design and study of efficient and environmentally benign Ag- and CeO2-containing NCs reduction catalysts supported on graphene oxide (GO). The silver- and/or ceria-containing catalysts are synthesized using deposition-precipitation onto GO prepared by oxidative treatment of graphite. The catalysts and support are characterized by XRD, XPS, TGA, N2 sorption, Raman spectroscopy, and UV–VIS spectrometry. The influence of state and the interaction of the active components on catalytic activity is thoroughly estimated in 4-nitrophenol (4-NP) reduction into 4-aminophenol (4-AP) at ambient pressure and room temperature. Nanosized Ag and CeO2 particles with sizes up to 30 and 5 nm, respectively, in the GO structure are obtained. The co-deposition of Ag and CeO2 onto GO promotes the stabilization of silver in the catalyst. The Ag-CeO2/GO catalyst demonstrates superior activity in the synthesized series (kapp of 1.615 and 3.674 min–1 for as-prepared and pre-reduced samples). In addition, the Ag-CeO2/GO catalyst retains good stability and a low leaching degree of the active components that makes these compositions efficient in NCs’ reduction into corresponding ACs